Communicative Language Teaching-Based Microteaching - Minda, Sri (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2026)
This study explores the effectiveness of Communicative Language Teaching (CLT)-based microteaching in improving students' communication skills in English. The purpose of this study was to analyze the effect of Communicative Language Teaching-based microteaching on students' speaking skills. Using an experimental design with a quantitative approach, this study involved a population of 7th semester students of the English Language Education Study Program at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, with a sample of 60 students selected randomly. The instruments used included a questionnaire, a speaking skills assessment rubric, and observations during the microteaching session. The data were analyzed using descriptive statistics and a T-test to compare the pre-test and post-test results between the experimental and control groups. The results of the analysis showed that the experimental group experienced a significant increase in speaking skills, while the control group only experienced minimal improvement. Observations also showed that this method increased students' active participation and created a more interactive learning environment. Thus, Communicative Language Teaching-based microteaching is proven to be effective in improving students' communication skills and building their confidence in speaking English.